1990
DOI: 10.1152/jappl.1990.68.6.2369
|View full text |Cite
|
Sign up to set email alerts
|

Is hypoxia a stimulus for synthesis of oxidative enzymes and myoglobin?

Abstract: To compare two situations with similar magnitudes of mitochondrial substrate flux but different blood oxygen contents, one-legged training was employed. Ten healthy subjects trained one leg under normobaric conditions and the other under hypobaric conditions. At each session the subjects trained each leg for 30 min. The absolute work intensity was the same for both legs and was chosen to correspond to 65% of the average (right and left) pretraining one-legged maximal work capacity. There were three to four tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
164
7
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(189 citation statements)
references
References 0 publications
12
164
7
6
Order By: Relevance
“…Similar capillary densities have been measured in human skeletal muscle [e.g., 286 cap/mm 2 (Celsing, 1988), 300-550 cap/mm 2 (Terrados, 1986, Terrados, 1990]. A higher capillary density has the potential to increase the LAP of Hb in skeletal muscle.…”
Section: Assumptionssupporting
confidence: 71%
See 1 more Smart Citation
“…Similar capillary densities have been measured in human skeletal muscle [e.g., 286 cap/mm 2 (Celsing, 1988), 300-550 cap/mm 2 (Terrados, 1986, Terrados, 1990]. A higher capillary density has the potential to increase the LAP of Hb in skeletal muscle.…”
Section: Assumptionssupporting
confidence: 71%
“…A higher [Mb] has the potential to accommodate the increased DO 2 needs in Type I fibers which are highly oxidative and tend to have a higher capillary and mitochondrial density. Terrados et al (1986Terrados et al ( , 1990 (Warriss, 1979, Reynafarje, 1963, Terrados et al, 1990, Celsing et al, 1988, Terrados et al, 1986. Van Beek-Harmsen et al (2004) To correct for the reduced capillary hematocrit at rest relative to systemic hematocrit the value of 0.5 was used, derived from direct observations of the resting capillary Hct of ~22% and systemic Hct of ~45% (Kindig and Poole, 2001, Russell et al, 2003, Kindig and Poole, 1998.…”
Section: Assumptionsmentioning
confidence: 99%
“…Some adaptations may facilitate endurance performance, whereas others are less bene®cial. Although equivocal, human studies have demonstrated that either hypobaric or normobaric hypoxia per se is responsible for increases in blood haemoglobin (Hb) concentration (Berglund 1992), muscle mitochondrial volume, capillary supply (Desplanches et al 1993), aerobic enzyme activities and myoglobin concentration (Terrados et al 1990), 2,3-diphosphoglycerate (Mairbaurl et al 1986), rate of free fatty acid mobilisation (Young et al 1982) or an elevated blood bu ering capacity (Favier et al 1995). Altitude acclimatisation improves physical performance at altitude (Pugh 1967;Maher et al 1974), but the e ects on sea-level performance are less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that evaluated the interaction between hypoxia and myoglobin have yielded conflicting results (14,26,43). As outlined previously, selected animal and human studies suggest that myoglobin expression is induced in response to hypoxia.…”
mentioning
confidence: 99%